Preferred lattice misorientations in rolled aluminium: tracking experiments and crystal plasticity simulations. Issue 1 (July 2015) - Quey, R; Dawson, P; Driver, J H
Abstract: The microstructural heterogeneities developed in the grains of hot deformed Al have been quantified by applying the microtexture tracking technique to hot plane strain compressed Al-0.1%Mn. By successive EBSD measurements over the same (internal) surface at different strains, a large data set of lattice orientation and disorientation development has been obtained in over 150 grains up to strains of 1.2. Simultaneously, high resolution finite element simulations have been carried out to large strains with the same grain orientations; both experiments and simulations focus on the orientation distributions developed within individual grains. It is shown that 15-20% of the grains undergo orientation splitting, usually when the orientation is both symmetrical with respect to the loading and divergent in terms of potential lattice rotations. An analysis of the reorientation velocity field predicted for hot PSC provides a first order indication of the particular grain orientations expected to undergo orientation splitting together with their splitting modes. In the majority of grains which simply undergo orientation spreading, a detailed analysis of the disorientation axes within grains has been carried out. At low strains, there is a very high density of near TD disorientation axes which progressively evolve with plastic strain towards RD. A similar, although faster, evolution to both RD and ND is predicted by the FECP simulations. Original explanations for these low and high strain disorientation axes are proposed, based first on the influence of random local stress variations on lattice rotations and then on the reorientation velocity field.